Aligning information technologies with evidence-based health-care activities: A design and evaluation framework - Sedig, Kamran; Anthony, Anthony; Haggerty, Nicole (Human Technology, 2017)
Evidence-based health care (EBHC) has given rise to expectations that decision-making be tethered to more high-quality information. As health information technologies (HITs) acquire an increasingly vital role in the information processes involved in EBHC, a more mature understanding is needed of the relationship between HITs and the EBHC activities they serve. In this paper, we conceptualize HITs and EBHC activities on a common foundation of distributed cognition that treats humans, technology, and the environment as interwoven parts of a whole, dynamic system. From that common foundation, we articulate a basis for achieving a contextually sensitive fit between HITs and EBHC activities by providing a framework (DETECT) of 20 properties that can be used to systematically characterize the fit between HITs and EBHC activities. Designers, deployers, and evaluators of HITs can use DETECT to better anticipate, locate, and diagnose the issues that arise when HITs are used to achieve diverse EBHC commitments.